First ultrasound report of temporal extension of bichat fat: correlation between anatomy and ultrasonography (Research, Society and Development, 2022)
The knowledge of facial anatomy and its correlation with ultrasonography has been gaining ground in the clinical practice of several professionals. Therefore, the knowledge of facial anatomical structures through dynamic ultrasonography images must be understood as a critical element for the clinical practice of guided esthetic facial procedures. In this pictorial essay focuses on discussing unprecedented anatomical details Temporal Extension of Bichat Fat correlating the anatomy with routine ultrasonography images. Knowledge of the US features of the temporal and buccal extensions of Bichat's fat will help narrow the differential diagnosis and guide clinical decision-making through spatial resolution and the ability to assess these structures using muscle contraction dynamically.